DESCRIPTION OF RIVER FLOW OF ARMENIA ALONG REGIONS OF BASIN MANAGEMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2006)
In the article descriptions of river flow of Armenia are given, which are created again along basin management, as well as activities of water balance, comparative description of hydrological, climatic peculiarities of these regions.
Keywords: river flow of Armenia; descriptions of river flow; water balance; climatic peculiarities